Cultivating Digital Fluency in Schools: Challenges and Sustainable Solutions - Anwar Dzikrullah; Fatimah Ramadhani; Prastio Efendi; Monoko Haguchi (Ihsan Cahaya Pustaka, 2025)
This study examines the integration of digital fluency in educational systems through an integrative model combining technical, pedagogical, and equitable access dimensions. Using a narrative literature review of interdisciplinary sources (2020–2025), the research identifies key challenges: infrastructure gaps, pedagogical misconceptions (e.g., the